Pengaruh Kualitas Layanan Internal dan Kepuasan Kerja terhadap Kinerja Karyawan Hotel - I Ketut Surata; Anak Agung Istri Manik Mahayani; I Gusti Agung Febrianto (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2020)
The aims of this study were to (1) analyze the influence of service quality to customer loyalty, (2) analyze the influence of service quality to customer satisfaction, (3) analyze the influence of customer satisfaction to customer loyalty, and (4) analyze the influence of service quality to customer loyalty with customer satisfaction as mediating variabel in Prime Plaza Suites Sanur – Bali. This study used questionnaires as the data collection techniques which were distributed to 100 guests who have stayed at Prime Plaza Suites Sanur – Bali as the respondents of this study. Data were analyzed quantitatively using classic assumption testing, simple linear regression analysis, t-test, path analysis and analysis of determination. The result of this study indicated (1) service quality has a positive and significant effect on customer loyalty (? = 0,257; t-value = 2,638; p < 0,05), (2) service quality has a positive and significant effect on customer satisfaction (? = 0,964; t-value = 30,814; p < 0,05), (3) customer satisfaction has a positive and significant effect on customer loyalty (? = 0,252; t-value = 2,617; p < 0,05) and (4) customer satisfaction has a partial mediating on the positive and significant relationship between service quality on customer loyalty ? = 0,961; t-value = 29,552; p < 0,05).